Organisational politics, organisational support and job satisfaction in an institution of higher education - Hlongwane, Minah (My University, 2021)
The purpose of this study was to examine the relationships among organisational politics, organisational support and job satisfaction among 148 participants in a selected institution of higher education in South Africa. Quantitative, descriptive research was conducted to determine if there is a relationship among the three variables of the study. Data collection was done using structured questionnaires. Two groups of respondents participated in the study; and that is the academic staff and administrative staff members from central administration and library. The study established that organisational politics is negatively related to organisational support and have a negative impact on the overall job satisfaction. Based on the findings of the study, recommendations, strengths and potential links for future research are provided. Key words/concepts: Organisational Politics, Organisational Support, Job Satisfaction.
Thesis (M. Com. (Human Resource Management)) -- University of Limpopo, 2021
Keywords: Organisational Politics; Organisational Support; Job Satisfaction; Job satisfaction -- South Africa; Employee-management relations in government; Office politics; Job enrichment; Personnel management -- South Africa